Effect of team-building sports games on the resilience of Chinese rural children: evidence from Nanxian county, Hunan province - Liu, Bo; You, Jizhi; Fan, Yunxiang; Xia, Yunping; Wang, Hui; Zhang, Xiang; Zhang, Yang (Frontiers in Pediatrics, 2025)
PurposeParticipation in competitive sports has been shown to enhance children's mental health. However, evidence regarding the impact of group sports within traditional physical education on children's mental development is scarce. This study designed a team-building-focused physical education program and examined its effects on the resilience of rural students.MethodsA total of 86 rural elementary school students (mean age: 11 years) were cluster-randomized into the intervention and control groups. Both groups participated in regular physical education classes three times per week. In the intervention group, the first 15-min warm-up period was replaced with sports games. From a social perspective, all games subtly encourage children to forge new social relationships by engaging in physical contact, interacting with new team members, and collaborating to achieve shared goals in a sportsmanlike manner. Resilience was assessed using the Resilience Scale for Chinese Adolescents before and after the 12-week intervention.ResultsAfter 12 weeks, the intervention group showed significant improvements in affect control, positive thinking, and help-seeking compared to the control group. Overall, both the individual and supportive dimensions of resilience improved following participation in team-building sports games.ConclusionsWhether winning or losing as a team member, these experiences positively enhance children's emotional regulation, their understanding of their social roles within a team, and the development of help-seeking and concern for a distressed other. As a result, children may build new and broader social connections that extend beyond the physical education class, fostering a sportsmanlike civic virtue in their daily lives.